Development of Hazard and Risk Simulation Applications in Electrical Power Installation Workshops Based on Android in Vocational High Schools - Susilowati, Brigitta Endah; Hartoyo, H. (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
This study aims to: (1) develop a hazard and risk simulation application, (2) find out the function test, (3) find out the feasibility of the hazard and risk simulation application, and (4) determine the effectiveness of using the hazard and risk simulation application. This research uses the Research and Development method with the ADDIE development model, according to Lee and Owens. It consists of 5 stages, including analysis, design, development, implementation, and evaluation. The research subjects were 70 students in the Electrical Power Installation Engineering Expertise Package at SMK Negeri 2 Yogyakarta. Data collection used a questionnaire that had been validated by media experts and material experts, each with two validators. Data analysis using descriptive methods. The results of the study concluded that: (1) the development of hazard and risk simulation applications can be used to support learning in the subject of Basic Electromechanical Work for Class X students, Competence of Electrical Power Installation Engineering Expertise, (2) function tests of hazard and risk simulation applications are included in the category of " Very Good", (3) the feasibility of the hazard and risk simulation application is included in the "Very Eligible" category according to media experts, material experts, and user response, (4) Wilcoxon test known Asymp value. Sig. (2-tail) of 0.00 shows that there is a difference in value after using hazard and risk simulation learning media. The effectiveness of media applications is known to have increased learning outcomes and is included in the "Moderate" category with a gain value of 0.43. This shows that the media application of hazard and risk simulation applications is effectively used as a learning medium to improve student learning outcomes.